2009
DOI: 10.1097/brs.0b013e318198ce10
|View full text |Cite
|
Sign up to set email alerts
|

Implant Complications, Fusion, Loss of Lordosis, and Outcome After Anterior Cervical Plating With Dynamic or Rigid Plates

Abstract: Dynamic cervical plate designs provide less implant complications (no patient) compared with rigid plate designs (4 patients). Speed of fusion was faster in the presence of a dynamic plate. However, loss of segmental lordosis is significantly higher if dynamic plates are used, which did not result in differences regarding clinical outcome between dynamic and constrained plates after 2 years. Thus, dynamic plates should be considered to be the preferred treatment option because of the lower risk for implant fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
0
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 17 publications
0
99
0
12
Order By: Relevance
“…The former include a higher fusion rate, particularly in multilevel cases, a better alignment of the cervical spine, with restoration or maintenance of lordosis, and the prevention of interbody graft/cage dislocation or subsidence [28]. Among the latter, dysphagia and tracheoesophageal lesions are the most frequently reported [9,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The former include a higher fusion rate, particularly in multilevel cases, a better alignment of the cervical spine, with restoration or maintenance of lordosis, and the prevention of interbody graft/cage dislocation or subsidence [28]. Among the latter, dysphagia and tracheoesophageal lesions are the most frequently reported [9,31].…”
Section: Discussionmentioning
confidence: 99%
“…Pitzen et al [28] analyzed the differences in fusion rates, complications and changes in segmental lordosis in patients treated with dynamic plates versus rigid ones. They found that when a dynamic plate is used the fusion process is faster and the implant-related complications are lower.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgeons also prefer to add an anterior plate to enhance rigidity of fixation especially in multi-level cases (11,23,24). Although the design of the current anterior plate has been improved over the years, the complications related to the plates are still not rare, and include screw loosening or breakage, plate breakage, and screw pullout with or without migration into the gastrointestinal tract (15,25).…”
Section: █ Resultsmentioning
confidence: 99%